Pengembangan sistem pakar menggunakan Metode Forward Chaining untuk penelusuran dan publikasi manuskrip ilmiah pada Jurnal Internasional Bereputasi - Iwan Suhardi; Sapto Haryoko; Hendra Jaya (Seminar Nasional LP2M UNM, 2019)
The purpose of this study was to find out: 1) How to develop an Expert System for Searching and Publishing Scientific Manuscripts on Reputable International Journals for Lecturers in Makassar State University; 2) How can the Expert System with the Forward Chaining method facilitate Faculties in publishing Scientific Manuscripts so that they can be published in reputable international journals; 3) How to design an Expert System for Searching and Publishing Scientific Manuscripts in Reputable International Journals for Makassar State University Lecturers meet valid, practical, and effective criteria. The first year research is a type of research and development. Software development in the form of Expert Systems with Forward Chaining Methods for Searching and Publishing Scientific Manuscripts in Reputable International Journals is carried out with an engineering approach where the stages are: analysis, design, implementation, and evaluation. After generating an Expert System Using the Forward Chaining Method for Searching and Publishing Scientific Manuscripts on Reputable International Journals for Lecturers in Makassar State University. Based on the research that has been carried out in the development of expert system applications for the search and publication of scientific manuscripts on reputable international journals, the researcher can draw several conclusions, namely: 1) Expert Systems for Searching and Publishing Scientific Manuscripts on Reputable International Journals for Makassar State University Lecturers developed with using a linear sequential software development model, also known as the waterfall model. The stages of development in this model include the process of knowledge analysis, design, coding or implementation, and implementation; 2) Expert System with Forward Chaining method can facilitate Lecturers in publishing Scientific Manuscripts so that they can be published in reputable international journals; 3) Expert System Design for Searching and Publishing Scientific Manuscripts on Reputable International Journals for Makassar State University Lecturers meet valid, practical criteria. The appropriateness of the application is measured using software eligibility criteria. The appropriateness test of the application by the developer includes aspects of functionality. The functionality aspect based on the testing that has been done, getting the test results is very good. All existing functions can work well.